Estimated age of first exposure to American football and outcome from concussion. (24th November 2020) - Caccese, Jaclyn B.; Houck, Zac; Kaminski, Thomas W.; Clugston, James R.; Iverson, Grant L.; Bryk, Kelsey N.; Oldham, Jessie R.; Pasquina, Paul F.; Broglio, Steven P.; McAllister, Thomas W.; McCrea, Michael; Hoy, April Marie (Reed); et al.
Abstract : Objective: To examine the association between estimated age at first exposure (eAFE) to American football and clinical measures throughout recovery following concussion. Methods: Participants were recruited across 30 colleges and universities as part of the National Collegiate Athletic Association (NCAA)–Department of Defense Concussion Assessment, Research and Education Consortium. There were 294 NCAA American football players (age 19 ± 1 years) evaluated 24–48 hours following concussion with valid baseline data and 327 (age 19 ± 1 years) evaluated at the time they were asymptomatic with valid baseline data. Participants sustained a medically diagnosed concussion between baseline testing and postconcussion assessments. Outcome measures included the number of days until asymptomatic, Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) composite scores, Balance Error Scoring System (BESS) total score, and Brief Symptom Inventory 18 (BSI-18) subscores. The eAFE was defined as participant's age at the time of assessment minus self-reported number of years playing football. Results: In unadjusted regression models, younger eAFE was associated with lower (worse) ImPACT Visual Motor Speed ( R 2 = 0.031, p = 0.012) at 24–48 hours following injury and lower (better) BSI-18 Somatization subscores ( R 2 = 0.014, p = 0.038) when the athletes were asymptomatic. The effect sizes were very small. The eAFE was not associated with the number of days until asymptomatic, other ImPACT composite scores, BESS total score, or other BSI-18 subscores. Conclusion: Earlier eAFE to American football was not associated with longer symptom recovery, worse balance, worse cognitive performance, or greater psychological distress following concussion. In these NCAA football players, longer duration of exposure to football during childhood and adolescence appears to be unrelated to clinical recovery following concussion.